P764 Drug level thresholds in patients with Crohn's disease on dose-intensified anti-TNF therapy predict intestinal wall healing for infliximab but not adalimumab. (16th January 2018) - Little, R; Su, H; Friedman, A; Williams, S; Gibson, P; Ward, M; Taylor, K; Sparrow, M
Abstract: Background: Secondary loss of response to infliximab (IFX) or adalimumab (ADA) occurs in up to 30–40% of patients with Crohn's disease (CD). Recapturing response, with subsequent disease quiescence, may be achieved via dose-escalation of anti-TNF therapy. We sought to determine the target drug level and drug level increment associated with quiescence on intestinal ultrasound (IUS) in patients with CD receiving dose-intensified IFX or ADA for secondary loss of response. Methods: Retrospective observational study of CD patients with secondary loss of response receiving dose-intensified anti-TNF therapy (IFX 5 mg/kg 6 weekly, ADA 40 mg weekly) for a period between September 2013-March 2017. IUS and trough drug level were measured at baseline and every 6 months after dose escalation. IUS were graded based on a global assessment of bowel wall thickness and stratification, hyperaemia on colour Doppler, mesenteric hyperechogenicity and lymphadenopathy. Patients were dichotomised into one of two groups based on their most recent IUS: quiescent or active. Non-parametric tests were used for intra- and inter-group comparisons and Receiver Operating Characteristic analyses to identify a threshold drug level and drug level increment from baseline associated with quiescence. Results: Of 35 patients (49% male, mean age 41 years), 54% used IFX and 74% concomitant immunomodulation. 22 patients (63%) had quiescent disease on their most recent IUS. There were no significant differences in demographics, baseline drug levels or baseline IUS activity between quiescent and active groups. Absolute IFX drug levels and the increment from baseline were significantly higher in the quiescent compared with the active group, but no such differences were observed for ADA (Table 1). IFX level ≥4.8 μg/ml or increasing drug level by ≥5.5 μg/ml from baseline best predicted IUS quiescence (AUC 0.79, sensitivity 77%, specificity 71% p = 0.04; AUC 0.85, sensitivity 80%, specificity 86% p = 0.02; Figure 1A). No such thresholds were identified with ADA (Figure 1B). Conclusions: After IFX dose intensification, CD patients maintaining or achieving IUS quiescence had greater absolute and incremental drug levels than those with active disease. While targeting an IFX drug level of ≥4.8 μg/ml predicted quiescence, ADA drug levels were not predictive of sonographic activity.